HEADING TOWARDS SDGS ACHIEVEMENT: EVALUATING INSTITUTIONAL CAPACITY IN IMPLEMENTING COASTAL ECONOMIC DEVELOPMENT POLICIES IN BIMA REGENCY - Usman, Ahmad; Haeril, Haeril (KOMUNITAS, 2024)
This study explores the necessity and techniques for enhancing institutional capacity in implementing policies for coastal economic development in Bima Regency, aimed at achieving Sustainable Development Goals. Coastal economic development is crucial for the attainment of SDGs, especially in resource-rich but institutionally challenged areas like Bima Regency. Utilizing a mixed-methods approach, this research integrates interviews, focus group discussions, and document analysis to assess current institutional capabilities and develop strategies to boost these capacities. The findings reveal that the government of Bima Regency excels in delivering quality public services, maintaining financial stability, and fostering employee competence. However, it struggles with over-reliance on central funding and limited cross-sector collaboration. This study identifies opportunities in regional partnerships, tourism expansion, and technology use, while acknowledging threats from national policy shifts and environmental vulnerabilities. By enhancing strengths, mitigating weaknesses, and exploiting opportunities, Bima Regency can model regional progress towards SDGs and sustainable community welfare improvement.